Analisis Kesalahan Siswa Menyelesaikan Soal Cerita Materi Barisan dan Deret Aritmetika Kelas XI MIA SMA Al-Ikhlas Lubuklinggau - Murni Anita Sari; E Efuansyah; Nur Fitriyana (Universitas Tamansiswa Palembang, 2020)
Abstract: This study aims to find out what types of errors and factors cause students to make mistakes in solving the arithmetic sequence and sequence material for class XI MIA SMA Al-Ikhlas Lubuklinggau. The research method used is descriptive qualitative. Data collection techniques in research using observation, interviews and documents. Data analysis procedure with the steps: data reduction, data presentation and conclusion. The results showed that there were errors made by students of class XI MIA SMA Al-Ikhlas Lubuklinggau in solving story questions about arithmetic sequences and series, namely: errors in understanding questions (49.99%), question transformation (50%), operation process (79.16 %) and writing the final answer (88.89%). The overall average error is (67.01%) with the high category. Based on the results of the interview the causes of students made mistakes, namely: students forgot and were unable to write information into mathematical symbols, did not know the formulas that should be used in the questions, were in a hurry because time was running out, were not careful, were mistaken in writing the operation signs, did not know which steps were must be done, forgetting to write down conclusions, and consider the final answer only to get the value that is sought. Keywords: Analysis, Errors, Problem Stories, Sequences and Arithmetic Series.